2019
DOI: 10.1002/aet2.10324
|View full text |Cite
|
Sign up to set email alerts
|

Direct Observation Assessment of Ultrasound Competency Using a Mobile Standardized Direct Observation Tool Application With Comparison to Asynchronous Quality Assurance Evaluation

Abstract: Objectives: Competency assessment is a key component of point-of-care ultrasound (POCUS) training. The purpose of this study was to design a smartphone-based standardized direct observation tool (SDOT) and to compare a faculty-observed competency assessment at the bedside with a blinded reference standard assessment in the quality assurance (QA) review of ultrasound images. Methods: In this prospective, observational study, an SDOT was created using SurveyMonkey containing specific scoring and evaluation items… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 17 publications
0
19
0
Order By: Relevance
“…Incorporating an SDOT on a scheduled basis ensures consistency of the evaluation across learners. A recent study demonstrated that measuring clinical ultrasound competency via in situ clinical observation as measured by SDOT correlated well with assessment via asynchronous image review …”
Section: Resultsmentioning
confidence: 99%
“…Incorporating an SDOT on a scheduled basis ensures consistency of the evaluation across learners. A recent study demonstrated that measuring clinical ultrasound competency via in situ clinical observation as measured by SDOT correlated well with assessment via asynchronous image review …”
Section: Resultsmentioning
confidence: 99%
“…While structured assessment methods for POCUS assessment exist, few have undergone robust evaluation, and none are in widespread use. [9][10][11][12][13][14] In conjunction with the content experts on the CAEP EUC, we used modified Delphi methodology to create a universally applicable, simple, entrustment-based, POCUS competency assessment tool and subsequently piloted it in an OSCE scenario.…”
Section: Discussionmentioning
confidence: 99%
“…Although there are no prior data comparing these 2 devices, prior literature has demonstrated an interpretability of 89% in resident ultrasonographers. The variance was not reported 8 . Assuming a variance of 10% in this cohort, a sample size of 50 would be able to detect a 6% difference in interpretability between handheld and traditional groups with power of 0.8 and alpha of 0.05.…”
Section: Methodsmentioning
confidence: 91%